Rupture of sigmoid colon with evisceration of bowel loops through the anus - Kumar, Naresh; Samy, Karuppa; Kumar, Vinoth (International Surgery Journal, 2016)
Spontaneous rupture of sigmoid colon with small bowel evisceration through anus is rare and an acute gastrointestinal emergency. It occurs in patients with rectal prolapse. Protrusion of loops of small bowel through the anal orifice is usually associated with spontaneous rupture of the distal sigmoid colon or rectum caused by a sudden increase of intra-abdominal pressure.